Gaya Komunikasi Guru dalam Meningkatkan Motivasi Belajar Siswa SD Negeri 165 Asanae Soppeng - Mahmud Mahmud; Fatmawati Fatmawati; Syahril Syawal (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Teaching and learning styles are behaviors or actions that teachers and students show during learning. Behavioral teaching reflects teachers' beliefs and values in translating science. Student behavior provides insight into how to perceive, interact, and respond to the environment in which learning occurs. The purpose of the research was to find out how the Teacher's Communication Style in Increasing the Learning Motivation of Class I Students of UPTD SPFSD Negeri 165 Asanae Marioritengnga Village, Soppeng.The research method used is a quantitative research method with a descriptive approach with in-depth interview data collection techniques, observation and documentation. Meanwhile, the data analysis technique used is the Miles and Huberman version which includes: data reduction, data display, and conclusion drawn. The results of the study show that teachers in communicating with their students apply various communication styles, including teachers providing initial direction, but providing space for students to take initiative, explore, and determine the course of learning. This style encourages students to develop independence and problem-solving. In accordance with the concept of independent learning where learning no longer focuses on the teacher but learning focuses on students, Becoming a reliable communicator in the classroom, Asking questions briefly and clearly, Applying the discussion learning method in the classroom, Applying the debate learning method in the classroom, Applying presentation learning..